West African Monetary Policy, External Shocks and Economic Growth Dynamics: An S-var Model - Abdullahi Bashir Muhammed; Umar Mohammed Tela; Siti Nur Aqilah Ab Wahab (Penerbit UMS, 2022)
As a result of the West African region's continuous political and economic instability, various economies have used monetary policy changes to respond to shocks from macroeconomic causes. Scholars disagree on the mechanisms of monetary policy, external shocks, and macroeconomic activity links in an economy, according to the available literature in both inter-regional and intra-regional evaluations. This article promotes understanding and management of external shocks in monetary policy by focusing on two key goals. (1) To investigate external shocks, macroeconomic performance, and the dynamics of monetary policy in Western African countries. (2) Use the S-VAR method of estimate to investigate the impact of these economic indices on monetary policy dynamics in Nigeria, Ghana, Cameroon, and Niger. The S-VAR method was chosen because it is useful for analysing macroeconomic shocks and monetary policy transmission. The findings reveal that the West African countries are so interconnected, any change in the price of non-oil commodities would have a significant impact on the exchange rate, which will be channelled through policy rates to GDP. We recommend and emphasise the need of diversifying member countries' productive and export bases rather than continuing to rely on one or a few items as the primary source of income.